Pengembangan Sistem Penyulingan Bahan Bakar Bioetanol dari Sampah Organik Pertanian di Desa Sempajaya, Kecamatan Berastagi, Kabupaten Karo: Indonesia - Sidabutar, Rivaldi; Trisakti, Bambang; Irvan, Irvan; Hanum, Farida; Surya, Indra; Taslim, Taslim; Sinaga, Mersi Suriani; Rizky, Muhammad Rafly; Sitepu, Lusti Angelica; Juniansyah, Muhammad Fadhillah; Abdurrahman, Muhammad Faiz; Syafutra, Wahyu Pramudya; Marbun, Daniel S (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Unsold vegetable waste from agricultural products generally rots and ends up in landfills, increasing waste volume and creating environmental problems. Utilizing vegetable waste as a raw material for bioethanol is a potential alternative, considering that bioethanol is a renewable energy source that can be produced through a biomass fermentation process. This study designed a 15 liter bioethanol production unit utilizing various types of vegetable waste, such as potatoes, pineapples, carrots, mustard greens, and cabbage. The process unit consists of pre-treatment equipment (a pre-cooking tank, a crusher, and a pressure tank), a fermenter equipped with two 30 cm diameter paddle-type manual stirrers, and a stainless steel distillation unit equipped with a heater and cooling tank. The fermentation process lasts for 48–72 hours and produces bioethanol with a concentration of 45%. This program is expected to provide dual benefits: as a solution for vegetable waste management to reduce environmental impacts and as a source of additional income for the community through the utilization of the bioethanol produced.